Answer:
-20
Explanation:
Well we are given that is a quadratic equation.
We are also given f(4) = 0. This means 4 is one root of the quadratic.
We can factor the quadratic into a form like this:
f(x) = a (x - r) (x - 4)
Where r is the other root of the quadratic.
We can subsitute 1 and 7 into the quadratic because we are given that
f(1) = - 24 and f(7) = 60.
We will get the following:
-24 = a (1 - r) (-3)
and
60 = a (7 - 4) (3)
To get rid of the "a" term, we can divide the second equation by the first, giving us the following equations:
- 5/2 = - (7 - r) / (1 - r)
We can multiply both sides by 2 (1 - r).
This gives us:
-5 ( 1 - r) = -2 (7 - r), so
5r - 5 = 2r - 14, so
3r = -9.
Then, we know r = -3.
We can then derive that the unique quadratic with the desired values is:
f(x) = 2 (x + 3) (x - 4).
We can plug in x = -1, so we get f(-1) = (2) (2) (-5) = -20.
Thus, our answer is -20.
To be honest, the first way or the other soultion the one I thought of first. In the middle of doing this problem for fun, I discovered this simpler way.